Throwing Speed of Kosovo Handball According to Playing Position - Jeton Havolli; Primoz Pori; Sami Sermaxhaj; Bujar Begu (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2021)
The goal of this paper was to assess the throwing speed of the ball without jumping, and three steep jumps by playing position (backcourt, wing, pivot, and goalkeeper) In this research, we measured 93 players from Kosovo's elite league (22±4.70 years old; training experience 8.30±4.29 years; body height 183±7.83 cm; weight 84±13.74 kg); measurements were made with a radar speed gun. The results obtained were analysed through descriptive statistics for morphologic parameters, but throwing speed was analysed using ANOVA and the Kruskall-Wallis post hoc test. The overall average throwing speed without jumping was 85.67±8.13 km/h, while throwing seed with three-step jump was 84.20±8.68 km/h. measured by the radar gun. Without jumping back-court players have been distinguished compared to wingers and goalkeepers while there were no significant differences with pivots. Also, almost the same results have been achieved in the throwing speed of jump shot. As differences in throwing speed have been established according to the playing positions, we think the exercises for each posi- tion should also be differentiated.